Dui menre in the Bugis Wedding Tradition: Anregurutta Daud Ismail’s Perspective in Tafsir Al-Munir - Junaid, mursalim*; Sah , Moh. Arief; Apriliani, Nelly Ayu; Hafid, Abdul; Rahman , Syahrul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Dui menre/dui balanca is an important marriage tradition in Bugis society that often gives rise to tensions between customary practice and Islamic law, especially when its amount becomes a social and economic burden. This study aims to analyze the response and intellectual position of AGH. Daud Ismail as a prominent Bugis scholar and mufassir towards the Dui menre tradition through his Bugis-language exegesis, Tafsir al-Munir. Employing a qualitative approach, this study draws on the frameworks of hermeneutics and Islamic legal anthropology, in particular, the concepts of al-‘urf (custom) and al-maslahah (public benefit), as analytical lenses. Hermeneutics is used to reveal the meaning contained in Tafsir al-Munir in the socio-cultural context of Bugis society while Islamic legal anthropology is used to study the practice of Dui menre as a local custom. The data were collected through literature review and in-depth interviews. The main source analyzed was Tafsir al-Munir by AGH. Daud Ismail, supported by journal articles, books and other relevant scientific works. In-depth interviews were carried out with a number of informants, including ulama (Islamic scholars) who had studied directly under AGH. Daud Ismail, academics, and religious figures. The findings reveal that AGH. Daud Ismail is of the opinion that the tradition of uang panai is permissible (mubah) based on the principle of al-‘adah al-muhakkamah so long as it does not conflict with the values of sharia and does not cause harm. From the perspective of hermeneutics and anthropology of Islamic law, this interpretation is a symbol of a pattern of integration (tahmil) between adat and sharia through accommodative-critical negotiation based on the principles of assimaturuseng (agreement), asitinnajang (propriety), assicocokong (compatibility), assiwollong pollongeng (close social interaction), and sipakalebbi (mutual respect). This study thus confirms the relevance of Tafsir al-Munir as a model for harmonizing Islamic law and local culture.